Understanding Sciences Through Participatory Research. - ramenah, harry (Advances in Social Sciences Research Journal, 2019)
The interest for a researcher to follow a participatory research approach compared to a conventional approach is multiple. The aim of this project is to make scientific research accessible to everyone, especially high school students. Our approach is a new concept of learning by doing for high school students that adopt the posture of a researcher to solve a problem presented to them. Students propose working hypotheses, imagine their protocol, experiment, discuss and communicate their results. High school students are supervised by the PhD students and the results from these studies are used for their research work. Currently several French and international Universities have approached us to implement this participatory research.